Učenje ter uporaba čitalniškega gradiva v čitalnici šolske knjižnice Osnovne šole Prule - Škrlj, Gregor (Šolska knjižnica, 2014)
The paper aims to present the reading-room, the importance that both, the reading-room and its materials are used in teaching and other school work. It present the reading-room materials, and its physical arrangement and avilability. It describes an example of an entire school year where each class received one hour of the Library and information knowledge in the readingroom. It also briefly mentions the modern part of the reading-room collection - the ICT eqipmment, namely e-reader, tablet computers, and i-blackboard. To achieve learning goals and for appropriate use of the materials it is important that the pupils know various types of materials, and distinguish them according to purpose. It is very reccomendable to prepare the criteria to identify which library materials should be put in the reading-room collection.
Keywords: čitalnice; IKT; informacijsko-komunikacijska tehnologija; knjižnično gradivo; osnovne šole; šolske knjižnice